Impact Assessment of Trainings on Rural Women for Value Added Pearl Millet Products - Preeti Malik , SK Varma and Vinita Jain, (Indian Journal of Extension Education, 2015)
Pearl millet grains are very high in calories- precisely the reason they do wonders for growing children and pregnantwomen. Iron deficiency, which is widely prevalent in India, impairs children's physical growth, mental development, andlearning capacity. Anemia is often induced by iron deficiency, and when severe it can increase women's risk of dying inchildbirth. It is a significant source of dietary energy and nutritional security for poor farmers and consumers in severalhighly populated regions of India. Pearl millet with elevated iron levels can help reduce iron deficiency and to someextent, zinc deficiency, in regions of India where it is a staple food crop. Pearl millet is a gluten free grain and is the onlygrain that retains its alkaline properties after being cooked which is ideal for people with wheat allergies.